Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

solve by substitution
-2x+4y+6=0
x-5y+3=0


Sagot :

naǫ
[tex]-2x+4y+6=0 \\ x-5y+3=0 \\ \\ \hbox{solve the 1st equation for x:} \\ -2x+4y+6=0 \ \ \ |-(4y+6) \\ -2x=-4y-6 \ \ \ |\div (-2) \\ x=2y+3 \\ \\ \hbox{substitute 2y+3 for x in the 2nd equation:} \\ 2y+3-5y+3=0 \\ -3y+6=0 \ \ \ |-6 \\ -3y=-6 \ \ \ |\div (-3) \\ y=2 \\ \\ x-5y+3=0 \\ x-5 \times 2+3=0 \\ x-10+3=0 \\ x-7=0 \ \ \ |+7 \\ x=7 \\ \\ (x,y)=(7,2)[/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.